Intergenerational Subalternity and the Resistance of Balinese Women in the Novel Racun Puan - Devy Selpia (LITERA KULTURA : Journal of Literary and Cultural Studies, 2026)
The novel Racun Puan by Ni Nyoman Ayu Suciartini presents the stories of three Balinese women across generations: Ibu Aruna, Aruna, and Samudra. Each of them is subjected to a distinct yet interconnected form of silencing, forming a chain of intergenerational subalternity. This study applies Gayatri Spivak's postcolonial theory to examine two aspects: the identification of Balinese women as subaltern figures in the novel Racun Puan, and the forms of resistance enacted by those subaltern characters. A qualitative descriptive-analytical method was employed, with data gathered from the novel through reading, observation, and documentation techniques. Analysis was conducted through Spivak's key concepts of political and cultural representation, epistemic violence, and resistance. The findings demonstrate that subalternity operates across generations through the internalization of patriarchal values, a process this study terms "intergenerational epistemic subalternity." Ibu Aruna, silenced by the intersection of caste stigma and domestic violence, unconsciously transmits the ideology of submission to Aruna, who is subsequently silenced by her husband's household and the broader patriarchal narrative. Aruna, in turn, reproduces a controlling parenting pattern toward Samudra. Each generation's resistance differs in form: Ibu Aruna resists through endurance and preserving educational access for her children; Aruna resists through diary writing as counter-discourse; and Samudra enacts the most transformative resistance by pursuing psychiatry and consciously reclaiming her own subjectivity. This study contributes a new analytical perspective that subalternity is not merely individual but can be reproduced across generations through subtle epistemological mechanisms embedded in family systems and cultural values. Keywords: subaltern, intergenerational subalternity, Balinese women, postcolonial, resistance